DIGITALIZATION AND DIGITAL TECHNOLOGY IN EDUCATION - SERAFÍN, Čestmír; DEPEŠOVÁ, Jana (Trends in education, 2018)
Technology is increasingly associated with digitisation today as logical instance technological development. Digital technology changing economy and society. These changes will inevitably affect the functioning of the society and life of all individuals. This means new opportunities and development of innovative services that have an impact on the quality of life. It is essential that the education system to respond to changing company affected by digital means of communication and work. Digital world must therefore be adapted to the education of children, pupils, students and teachers. On the issue of digital literacy in English education. The basic strategy, which makes its development and added to look at reality in education own research investigation.
Keywords: Education; Education 4.0; eDidactics digitalization; digital technology